Symmetries and conservation laws of certain classes of nonlinear Schrödinger partial differential equations - Masemola, Phetego (My University, 2013)
Unable to load abstract.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, in fulfilment of the requirements for the degree of Master of Science. Johannesburg, 2012.
Keywords: Differential equations, Partial.; Conservation laws (Mathematics); Schrödinger equation.; Symmetry.